Clinical performance of lung ultrasound in predicting ARDS morphology - Costamagna, Andrea (Ann Intensive Care, 2021)
BACKGROUND: To assess diagnostic performance of lung ultrasound (LUS) in identifying ARDS morphology (focal vs non-focal), compared with the gold standard computed tomography. METHODS: Mechanically ventilated ARDS patients undergoing lung computed tomography and ultrasound were enrolled. Twelve fields, were evaluated. LUS score was graded from 0 (normal) to 3 (consolidation) according to B-lines extent. Total and regional LUS score as the sum of the four ventral (LUS(V)), intermediate (LUS(I)) or dorsal (LUS(D)) fields, were calculated. Based on lung CT, ARDS morphology was defined as (1) focal (loss of aeration with lobar distribution); (2) non-focal (widespread loss of aeration or segmental loss of aeration distribution associated with uneven lung attenuation areas), and diagnostic accuracy of LUS in discriminating ARDS morphology was determined by AU-ROC in training and validation set of patients. RESULTS: Forty-seven patients with ARDS (25 training set and 22 validation set) were enrolled. LUS(TOT), LUS(V) and LUS(I) but not LUS(D) score were significantly lower in focal than in non-focal ARDS morphologies (p < .01). The AU-ROC curve of LUS(TOT), LUS(V), LUS(I) and LUS(D) for identification of non-focal ARDS morphology were 0.890, 0.958, 0.884 and 0.421, respectively. LUS(V) value ≥ 3 had the best predictive value (sensitivity = 0.95, specificity = 1.00) in identifying non-focal ARDS morphology. In the validation set, an LUS(V) score ≥ 3 confirmed to be highly predictive of non-focal ARDS morphology, with a sensitivity and a specificity of 94% and 100%. CONCLUSIONS: LUS had a valuable performance in distinguishing ARDS morphology. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13613-021-00837-1.